Performance evaluation of full-scale tuned liquid dampers (TLDs) for vibration control of large wind turbines using real-time hybrid testing. (1st November 2016) - Zhang, Zili; Staino, Andrea; Basu, Biswajit; Nielsen, Søren R.K.
Highlights: Performance evaluation of full-scale tuned liquid dampers carried out for wind turbines. Coupled blade-tower model considered in the numerical sub-structure. Stochastic turbulence due to rotationally sampled spectra considered. Effect of damping screens experimentally investigated. Experimental results compared with results from an analytical nonlinear model. Abstract: Tuned liquid dampers (TLDs) utilize the sloshing motion of the fluid to suppress structural vibrations and become a natural candidate for vibration control of large flexible wind turbines. Special structures such as wind turbine towers have characteristics and exhibit behavior which are significantly different from conventional civil engineering structures. In addition, the stochastic aerodynamic load generated from the turbulence is different from what is generated on conventional tall structures, due to rotationally sampled spectra. Experimental studies on the evaluation of full scale TLDs to control vibration of such special facilities like wind turbine towers are absent in literature. In this paper, the performance of a full-scale TLD in mitigating lateral tower vibrations of multi-megawatt wind turbines is evaluated through the real-time hybrid testing (RTHT). Lateral tower vibrations of wind turbines are normally lightly damped due to low or even negative aerodynamic damping, and large amplitude vibrations induced by wind and ocean wave loads in the lateral direction may significantly shorten the fatigue life of the tower. In the RTHT, the full-scale TLD is tested as the physical substructure while the wind turbine is modeled using a 13-degree-of-freedom (13-DOF) aeroelastic model. Wind turbines with 2 MW and 3 MW capacities have been considered and cases of the TLD with and without damping screens have been tested. Further, the effect of tuning ratios on the damper performance has been studied by changing the mean water level of the tank. Finally, comparison has been performed between the experimental results and the results from an theoretical model of the TLD-wind turbine system. The present study provides strong support and useful guidelines for the application of TLDs in large wind turbines.